Natural Resources Utilization Comic Media Based on Local Wisdom: Mount Kelud Kediri - Aka, Kukuh Andri; Aprilia, Hesinta Mita; Permana, Erwin Putera; Afandi, Zainal (Universitas Pendidikan Ganesha, 2023)
Social studies learning materials that utilize natural resources are minimal in learning media so student learning outcomes could be better. To overcome this problem, comic media based on the local wisdom of Mount Kelud has been developed. The purpose of developing comic media based on Mount Kelud Local Wisdom is to determine validity, effectiveness, and practicality. The research was conducted using R&D (Research and Development) research with the ADDIE development model. The research subjects were experts, teachers, and fourth-grade elementary school students. Collecting data using observation and questionnaire methods. The instrument used in collecting data is a questionnaire. The data analysis technique used is the quantitative analysis which is described qualitatively. The study results are that the average media validation results by media and material experts are 89%. The results of the effectiveness of using media through trials showed an increase in student learning outcomes reaching 87%. The average practicality results through teacher and student responses are 93%. Based on these results, the comic media based on the local wisdom of Mount Kelud that has been developed is valid, effective, and practical so that it is feasible to be used to support the learning process.